The Derivates Synthesis and Characterization of Some Schiff Base of Hexa-(2-Formyl–5-Methoxyphenoxy) Cyclotriphosphazene - Özen, Furkan; Koran, Kenan; Aslan, Fatih; Arslan, Mustafa (Osman SAĞDIÇ, 2014)
Hexa(2-formyl-5-methoxyphenoxy)cyclotriphosphazene (2) was obtained from the reaction of hexachlorocyclotriphosphazene (1) with 2-hydroxy-4-methoxybenzaldehyde in presence of K2CO3 at room temperature in THF under argon atmosphere. Schiff base containing phosphazene compounds (3-10) were synthesized by the reaction of hexa[(2-formyl-5-methoxy)phenoxy]cyclotriphosphazene (2) with 2-aminophenol, 4-aminobenzoicacid, 2-amino-5-methyl-1,3-thiazole, 4-aminobenzamide, 5-amino-1,3,4-thiazole-2-thiol, 2-aminobenzothiazole, 4-iminophenol and 4-iminoasetophenon respectively. The structures of the compounds were characterized by IR, 1H, 13C and 31P NMR spectroscopy and elemental analysis. Schiff base compounds could not be obtained from hexa[(2-formyl-5-methoxy)phenoxy]cyclotriphosphazene (2) with 2-amino-4-chlorophenol and 2-aminobenzimidazole.

Hekzaklorosiklotrifosfazen (1) ile 2-hidroksi–4-metoksi benzaldehidin THF’de K2CO3 beraberliğinde oda sıcaklığında argon atmosferindeki reaksiyonundan hekza(2-formil-5-metoksifenoksi)siklotrifosfazen (2) elde edildi. Hekza(2-formil-5-metoksifenoksi)siklotrifosfazenin (2), 2-aminofenol, 4-aminobenzoikasit, 2-amino–5-metiltiazol, 4-aminobenzamit, 5-amino-1,3,4-tiazol-2-tiyol, 2-aminobenzotiazol, 4-aminofenol ve 4-aminoasetofenon ile reaksiyonundan Schiff bazı taşıyan fosfazen bileşikleri (3-10) sentezlendi. Elde edilen ürünlerin yapıları IR, NMR(1H, 13C, 31P) ve elementel analiz ile aydınlatıldı. Hekza(2-formil-5-metoksifenoksi)siklotrifosfazen ile 2-amino–4-klorofenol ve 2-aminobenzimidazol’ün reaksiyonundan Schiff bazı elde edilemedi.
Hekza-(2-Formil–5-Metoksifenoksi)Siklotrifosfazen’in Schiff Bazı Türevlerinin Sentezi ve Karakterizasyonu
Keywords: Engineering; Mühendislik